Dampak Pembatasan Kampanye Bagi Pasangan Calon pada Pilkada Serentak 2020 - Maria Botifar; Poppi Damayanti; Robeet Thadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
ABSTRACT This study aims to evaluate the impact of campaign restrictions for the Bengkulu governor candidate pair in the simultaneous regional elections in 2020. The approach used is a qualitative descriptive method. There were 12 research informants from the winning candidate pair team, selected by purposive sampling. The results of the study show that the impact of limited meetings/face-to-face methods/dialogue, the candidate pair has the opportunity to be closer to the community it fosters, but it is less than optimal in reaching the number of voters and has limitations in introducing the candidate pair to the public directly, on the limitation of public debate, the positive debate is more directed because they are not influenced by supporting voices, more focused on content or material, presenters can be more focused in guiding, while the impact of limiting the distribution of campaign materials for each candidate pair is responded positively by each candidate, because the rules and regulations have not changed, even maintaining cleanliness of campaign material waste. The conclusion is that campaign restrictions for the Bengkulu governor and deputy governor candidates in the 2020 simultaneous regional elections have both positive and negative impacts, especially on restrictions on meetings, public debates and restrictions on the distribution of campaign materials and props to voters based on the campaign methods used. Keywords: Campaign Restrictions, Candidate Pairs, Pandemic Impact